Reevaluasi Hak-Hak dan Pembinaan Terhadap Narapidana Narkotika dalam Sistem Pemasyarakatan di Lembaga Pemasyarakatan Narkotika Kelas II A Yogyakarta - Tahir, Ach. (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2016)
It is generally known that  the rights  of inmates have  been well  executed  by  the  Wirogunan  penitentiary  in  Yogyakarta.  Some caveats  need  to  be  evaluated  by  the  Ministry  of  Justice and  Human Rights especially Directorate General of Corrections, there are medical service, less availability of decent food, the high cost of prison canteen food,  unresponsive  response  to  gripe,  complicated  remission procedure.It  also  needs  to  be  considered  in  developing  inmates  that some inmates never be the member of correctional institution before, upgrading facilities, coaching personality and autonomy theinmates it self.